Chemical attributes of a Hapludox soil after nine years of pig slurry application. - VEIGA, M. da (2012)
ABSTRACT: The objective of this study was to evaluate the pig slurry application effects on chemical attributes of a Hapludox soil managed under no-tillage system. Treatments consisted of 50, 100 and 200 m3 ha-1 per year of pig slurry application, and a control with replacement of P and K exported through harvested grains. Attributes related to soil chemical reaction, exchange complex, and nutrient contents were determined in soil samples collected in the ninth year of experimentation from 0–0.025, 0.025–0.05, 0.05–0.10, 0.10–0.20, 0.20–0.40 and 0.40–0.60 m soil depths. The continuous application of high doses of pig slurry on the Oxisol surface under no-tillage acidifies the soil and increases Al, P, Cu, and Zn contents down to 0.2-m depth, and K levels down to 0.6-m depth. RESUMO: O objetivo deste trabalho foi avaliar os efeitos da aplicação de dejeto líquido de suínos sobre os atributos químicos de um Latossolo Vermelho, sob sistema de plantio direto. Os tratamentos consistiram da aplicação de 50, 100 e 200 m3 ha-1 por ano de dejeto líquido de suínos, e de um controle, com reposição das quantidades de P e K exportadas nos grãos colhidos. Os atributos relacionados à reação química do solo, ao complexo de troca do solo e aos teores de nutrientes foram determinados em amostras de solo coletadas no nono ano de experimentação, a 0–0,025 e 0,025–0,05; 0,05–0,10, 0,10–0,20, 0,20–0,40 e 0,40–0,60 m de profundidade do solo. A aplicação contínua de altas doses de dejeto líquido de suínos na superfície de Latossolo Vermelho em sistema plantio direto acidifica o solo e aumenta os teores de Al, P, Cu e Zn, a 0,20 m de profundidade, e os de K a 0,60 m de profundidade.